Dynamic Clusters - Oliver Falck; Stephan Heblich (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2007)
Globalization has had an enormous impact on traditional industrial structures. It seems almost the case that everything is everywhere the same. And yet, in reality, some regions in a single industrialized country enjoy rapid economic growth while others are downsizing or stagnating. Thus there must be some remaining regional competitive advantages even in the 'Age of Globalization.' This paper engages in a quest to discover what these new 'locational' factors might be and how and why they are necessary in creating a dynamic cluster of regional growth. In doing so, we try to link agglomeration advantages of the new economic geography with competitive advantages of Porter's cluster theory. But we also go beyond these approaches and add further regional growth factors such as creativity or diversity. Using data that paint a comprehensive picture of industry and regional development in Germany we try to find empirical evidence for our approach. A case study from the automobile industry one of the leading industries in Germany completes our picture of dynamic clusters.
Keywords: R11; R12; O18; O33; 330; Cluster; Regional Growth; Innovation; Creativity